DIVERSITY OF BIVALVES AND GASTROPODS IN SONADIA ISLAND, BANGLADESH - Antu, Durjoy Raha; Islam, Tasfia Tanjim; Ahmed, Md Rasel; Ahmed, Sumaiya; Datta, Sujan Kumar; Ahmed, Md Sagir (Bioresearch Communications, 2022)
An attempt was made to explore the gastropods and bivalves diversity of Sonadia Island, an important habitat for molluscs. The study was carried out from January 2020 to December 2020. To determine the species abundance and richness, 8 transects were selected based on different habitat of bivalves and gastropods occupancy. A total of 89 species of bivalves (45) and gastropods (44) under 37 families and 15 orders have been confirmed. Veneridae (10 species) was the dominant family of bivalves where Muricidae and Turritellidae (5 species) of gastropods. About 1380 individuals of gastropods and bivalves were found in 8 transects. The highest number of species observed in transect 5 (35 species) which was about 45.45% of the total species. In case of abundance, transect 3 occupied the highest 730 individuals (54.97%). The highest species diversity was observed in transect 4 (H= 2.814 Ds= 0.9158) and the lowest was transect 2. Pirenella cingulate, Turritella duplicate and Cerithium columna were the most abundant species within the transect area. Among 8 transects, two large clusters and one small cluster were noticed that indicated species diversity varies at different habitats. During the study, two main threats were observed for the gastropods and bivalves diversity losses viz., collection of a huge number of live shells by the local people to make ornaments for the tourists of Cox’s Bazar, and destruc tion by local fishers during fishing through the coastal belt of the Island. Proper management is recommended for the conservation of bivalves and gastropod diversity. Bioresearch Commu. 9(1): 1225-1236, 2023 (January)